Cell wall bricks of defence: the case study of oligogalacturonides - Degli Esposti, Chiara; Guerrisi, Laura; Peruzzi, Giulia; Giulietti, Sarah; Pontiggia, Daniela (Frontiers in Plant Science, 2025)
The plant cell wall (CW) is more than a structural barrier; it serves as the first line of defence against pathogens and environmental stresses. During pathogen attacks or physical damage, fragments of the CW, known as CW-derived Damage-Associated Molecular Patterns (CW-DAMPs), are released. These molecular signals play a critical role in activating the plant’s immune responses. Among CW-DAMPs, oligogalacturonides (OGs), fragments derived from the breakdown of pectin, are some of the most well-studied. This review highlights recent advances in understanding the functional and signalling roles of OGs, beginning with their formation through enzymatic CW degradation during pathogen invasion or mechanical injury. We discuss how OGs perception triggers intracellular signalling pathways that enhance plant defence and regulate interactions with microbes. Given that excessive OG levels can negatively impact growth and development, we also examine the regulatory mechanisms plants use to fine-tune their responses, avoiding immune overactivation or hyper- immunity. As natural immune modulators, OGs (and more generally CW-DAMPs), offer a promising, sustainable alternative to chemical pesticides by enhancing crop resilience without harming the environment. By strengthening plant defences and supporting eco-friendly agricultural practices, OGs hold great potential for advancing resilient and sustainable farming systems.